(untitled) (Archive of Conferences, 2021)
The article deeply investigates the origin of foreign words in English texts embedded from other languages, historical peculiarities, problems and ways of their transmission into Uzbek. The main purpose of this article is considering theoretical concepts foreign words which have been researching heretofore.